2014
DOI: 10.1002/jor.22596
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional motion analysis of the patellar component in total knee arthroplasty by the image matching method using image correlations

Abstract: In total knee arthroplasty (TKA), the patella is significantly associated with range of motion and gait performance. Currently, no highly accurate methods are available that can measure the 3D in vivo behavior of the TKA patellar component, as the component is made of x-ray-permeable ultra-high molecular weight polyethylene. Previously, we developed a computer simulation that matches CT scan and unidirectional radiographic images using image correlations, and applied it to kinematic studies of natural and TKA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 31 publications
1
33
0
Order By: Relevance
“…The kinematics predictions of the model were in good agreement with current in vivo studies (Ishimaru et al, 2014;Sharma et al, 2012). The predicted and measured quadriceps force, and the patellofemoral and patellar tendon forces were also consistent with reported values (Fitzpatrick et al, 2014b;Frohm et al, 2007;Mason et al, 2008).…”
Section: Discussionsupporting
confidence: 84%
“…The kinematics predictions of the model were in good agreement with current in vivo studies (Ishimaru et al, 2014;Sharma et al, 2012). The predicted and measured quadriceps force, and the patellofemoral and patellar tendon forces were also consistent with reported values (Fitzpatrick et al, 2014b;Frohm et al, 2007;Mason et al, 2008).…”
Section: Discussionsupporting
confidence: 84%
“…Daniel et al [23] calculated by formula that the weight-bearing area should be in the area where the top of the femoral head overlaps with the acetabular cartilage surface, and can be affected The calculation method of weight-bearing area of femoral head in standing position mainly refers to the theoretical formula proposed by Genda et al [2], and the 3D reconstruction is realized by the principle of projection transformation and image registration. Ishimaru et al [25] reported simulating X-ray by projection transformation to create virtual radiographic image of 3D knee joint model and registering it with real X-ray film to realize visual reconstruction of polymer polyethylene patellar component and radiographically determine its external contour. Image registration is vital to the accurate construction of weight-bearing area in our modeling process, and obtaining X-ray, CT data of one volunteer in the same body posture is the premise of accurate registration.…”
Section: Discussionmentioning
confidence: 99%
“…The 3D positions and orientations of the pelvis and femur in movement cycle were determined by 3D-to-2D model-to-image registration technique using image correlations ( Figure 2 ). The relative geometric relationship between the X-ray source and the projection plane of the flat panel X-ray detector system was determined using a coordinate building frame [ 13 , 14 ]. Each subject was scanned by computed tomography (CT; Aquilion, Toshiba, Tochigi, Japan) with a 512 × 512 image matrix, 0.35 × 0.35 pixel dim, and 1 mm thickness spanning from superior edge of the pelvis to below the knee joint line ( Figure 2(c) ).…”
Section: Methodsmentioning
confidence: 99%
“…However, external markers attached to the skin could be affected by soft tissue artifacts with substantial errors [ 5 7 ]. Previous studies have reported direct measurement of skeletal kinematics from 3D surface models and radiographic image sequences [ 8 13 ]. However, no studies have employed 3D-to-2D model-to-image registration technique to analyze in vivo healthy hip kinematics.…”
Section: Introductionmentioning
confidence: 99%